Delirium and High Creatine Kinase and Myoglobin Levels Related to Synthetic Cannabinoid Withdrawal - Ahmet Bulent Yazici; Esra Yazici; Atila Erol (Case Reports in Medicine)
Synthetic cannabinoids (SCs) are included in a group of drugs called new psychoactive substances. Effects of SCs on the central nervous system are similar to other cannabinoids, but 2–100 times more potent than marijuana. Thus, addiction and withdrawal symptoms are more severe than natural cannabinoids. Withdrawal symptoms of SCs were reported in the literature previously. But there is no report about SC withdrawal delirium and its treatment. Several studies reported that agonists of CB1 receptors play a role in GABA and glutamatergic neurotransmission, which is similar to the effects of alcohol on GABA and glutamatergic receptors. Previous studies on alcohol delirium cases suggested that elevated creatine kinase (CK) can be a marker of progress. This study reports delirium and high serum CK levels related to SC withdrawal and offers a treatment with benzodiazepine for them. We described two cases treated in our inpatient clinic about SC withdrawal with increase of serum CK level and other laboratory parameters. One of them demonstrated delirium symptoms and the other did not with early rapid treatment.